2018
DOI: 10.1038/s41598-018-36982-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Creatine Kinase and Lactic Acid Dehydrogenase and Decreased Osteocalcin and Uncarboxylated Osteocalcin are Associated with Bone Stress Injuries in Young Female Athletes

Abstract: Stress fractures are a limitation for athletes not only in sports performance but in activities of daily living. Thus, preventing them is crucial. In female athletes, a triad of symptoms including low energy availability, functional hypothalamic amenorrhea and osteoporosis are considered risk factors for stress injuries, but biomarkers predictive of these outcomes are not available. Here, we evaluated 56 female university athletes and found that 13 had a history of stress bone injuries. Logistic regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Creatine phosphokinase enzyme consists of a dimer composed of two subunits (B and M) and has three isoforms: CK-BB or CK-1 found mainly in the brain; CK-MB or CK-2, hybrid form, mainly in the myocardium and CK-MM or CK-3 mainly in skeletal muscle. The reaction catalyzed by CPK is to reversibly phosphorylate creatine at the expense of ATP with the creation of creatine phosphate, especially at rest, so that during muscle activity, the reaction occurs in reverse, aiming at the synthesis of ATP (Miyamoto et al, 2018). When the intensity of the exercise is adequate to the metabolic capacity of the muscle tissue, F I G U R E 6 Behavior of CPK and LDH parameters during the moments evaluated in the case study.…”
Section: F I G U R Ementioning
confidence: 99%
“…Creatine phosphokinase enzyme consists of a dimer composed of two subunits (B and M) and has three isoforms: CK-BB or CK-1 found mainly in the brain; CK-MB or CK-2, hybrid form, mainly in the myocardium and CK-MM or CK-3 mainly in skeletal muscle. The reaction catalyzed by CPK is to reversibly phosphorylate creatine at the expense of ATP with the creation of creatine phosphate, especially at rest, so that during muscle activity, the reaction occurs in reverse, aiming at the synthesis of ATP (Miyamoto et al, 2018). When the intensity of the exercise is adequate to the metabolic capacity of the muscle tissue, F I G U R E 6 Behavior of CPK and LDH parameters during the moments evaluated in the case study.…”
Section: F I G U R Ementioning
confidence: 99%
“…CPK is a muscular enzyme that can be used to determine muscle deterioration or reduced muscular activity, and changes in CPK could support recent findings that bone and muscle exhibit crosstalk via OCN and RANKL. (32) In particular, OCN has been characterized as a key regulator of muscle mass and exercise adaptation. (7,10,18,33) However, much of the prior research was performed with only in one sex, or the sex of the mice was not described, which may explain why the sexual dimorphism of OCN removal or OCN+ cell ablation was not described before.…”
Section: Discussionmentioning
confidence: 99%
“…( 32 ) In particular, OCN has been characterized as a key regulator of muscle mass and exercise adaptation. ( 7,10,18,33 ) However, much of the prior research was performed with only in one sex, or the sex of the mice was not described, which may explain why the sexual dimorphism of OCN removal or OCN+ cell ablation was not described before. Female DT‐treated mice also showed an elevation of the liver enzyme ALT.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study has shown decreased OC and increased creatine kinase levels in trauma and bone injury. [ 33 ] OC was directly correlated with urine albumin to creatinine ratio patients with type 2 diabetes. [ 34 ] Thus, potential changes in renal filtration caused by trauma, which can be assessed by changes in creatinine excretion, might be a plausible explanation.…”
Section: Discussionmentioning
confidence: 99%